Presença de eventos estressantes de vida em crianças e adolescentes com dor abdominal recorrente - Patricia Cruz Guimaraes Pinto (2007)
The Non Organic Recurrent Abdominal Pain (NORAP) is a common problem in pediatric and infant gastroenterology centers. The aim of this study was to review the published literature about NORAP and the stressful life events considering moderator factors (social competence,parental somatic symptoms, copying). Twenty two articles were evaluated, 9 of the descriptive, 10 case-control studies, one cohort, one review and one randomized clinical trial. The children and adolescents aged from 1 to 19 years. The association between NORAP and stress showed disparity results, although, even the studies were stressful events did not differ organic and non organic abdominal pain, the studious concluded that the psychological stress is a important factor on the approach of those patients. The stressful life events mostly associated to NORAP were related to the family environment. The socio-economic factors showed contradictories results. The age showed a positive influence to the frequency of life events. The capacity of adaptation of a child and adolescent facing stress is a moderator factor in the pain perception. Higher levels of family stressors and parental somatic symptoms predict higher levels of somatic complaints by children. Among children and adolescent with high social competence, higher levels of family stressors were not associated with moresomatic complaints. Thus, the results shows that the early identification of the stressful life events and the moderator factors in children and adolescents with NORAP and a preventive and curative programs are important to evaluate this patients.